1998
DOI: 10.1002/(sici)1097-0142(19980425)84:2<115::aid-cncr8>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry in the cytologic evaluation of thyroid follicular lesions

Abstract: Preoperative quantitative estimations of cytologic nuclear features are useful for the preoperative differential diagnosis of follicular lesions of the thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 6 publications
3
28
0
4
Order By: Relevance
“…Using nuclear morphometry, we can quantify a number of parameters such as those related to nuclear size and shape. [8] It has been suggested that nuclear morphometric parameters such as nuclear area and perimeter,[910] nuclear area coefficient of variation,[11] and shape factors[11] may allow differentiation between thyroid lesions. Application of morphometry to cytology would be useful for the purpose of automated screening as well as accurate diagnosis of thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Using nuclear morphometry, we can quantify a number of parameters such as those related to nuclear size and shape. [8] It has been suggested that nuclear morphometric parameters such as nuclear area and perimeter,[910] nuclear area coefficient of variation,[11] and shape factors[11] may allow differentiation between thyroid lesions. Application of morphometry to cytology would be useful for the purpose of automated screening as well as accurate diagnosis of thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The NA and SD of each specimen were aggregated. The coefficient of variation of the nuclear area (NACV) was calculated as the objective parameter of anisonucleosis by the following formula: NACV (%) = (SD of NA)/(mean NA) x 100 [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Međutim, dalja istraživanja na ovom polju dala su kontradiktorne rezultate [14][15][16] . Kada su u pitanju PTC, većina autora se slaže da povećanje površine jedara tireocita ukazuje na malignu transformaciju ćelija 17,18 . Međutim, problem folikularnih neoplazmi i dalje je nerešen 19,20 .…”
Section: Uvodunclassified
“…U analizi bolesnika sa citološkom interpretacijom suspektno maligno, Nagashima i sar. 17,18 ne nalaze povezanost analizirane površine jedara i perimetra jedara sa određenim histopatološkim podtipovima folikularnih lezija. Izražena varijacija u površini jedara tireocita ogleda se u značajnim razlikama KVPJ tireocita između FTC i benignih lezija.…”
Section: Diskusijaunclassified